2015
DOI: 10.1111/jth.12861
|View full text |Cite
|
Sign up to set email alerts
|

Critical off‐target effects of the widely used Rac1 inhibitors NSC23766 and EHT1864 in mouse platelets

Abstract: Summary Background Platelet aggregation at sites of vascular injury is essential for normal hemostasis, but may also cause pathologic vessel occlusion. Rho GTPases are molecular switches that regulate essential cellular processes, and they have pivotal functions in the cardiovascular system. Rac1 is an important regulator of platelet cytoskeletal reorganization, and contributes to platelet activation. Rac1 inhibitors are thought to be beneficial in a wide range of therapeutic settings, and have therefore been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 42 publications
2
52
0
2
Order By: Relevance
“…1F). NSC23766 is a chemical inhibitor of the binding and activation of Rac1 GTPase, although it is not entirely specific for Rac1 (22;23). NSC23766 at a dose of 100 μM completely abolished Rac1 activity in AGS cells grown as spheroids (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…1F). NSC23766 is a chemical inhibitor of the binding and activation of Rac1 GTPase, although it is not entirely specific for Rac1 (22;23). NSC23766 at a dose of 100 μM completely abolished Rac1 activity in AGS cells grown as spheroids (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, NSC23766 [50 μM] also inhibited carbachol-induced RhoA activation and muscarinic acetylcholine-induced inotropic response in isolated neonatal rats requiring the activation of Rho-dependent kinases. More recent studies by Dutting and associates [45] have reported critical off-target effects of NSC23766 and EHT1864 [a known inhibitor of Rac1; ref. 46] in mouse platelets.…”
Section: Potential Caveats That We Need To Consider In Further Vamentioning
confidence: 99%
“…Under normal glucose condition, the dose of 30 μmol/L, NSC23766 was sufficient to reduce Rac1 activity, modulating, in turn, platelet function. Although the dose used in our study was significantly lower compared with the one used elsewhere,42 we cannot completely exclude that the potential off‐target effects of NSC23766 might affect our results. Because the effect of NSC23766 on platelet aggregation, under high glucose condition, is already present for lower NSC23766 doses (15 μmol/L), this raised the question of how to separate the effect of hyperglycemia and the effect of NSC23766 on platelet aggregation.…”
Section: Discussionmentioning
confidence: 81%